Spirituality and Perceived Supervisor Support as Predictors of Academic Integrity of Final-Year Undergraduate Students - Yonathan Natanael; Zulmi Ramdani; Nur'aini Azizah; Imas Fauzyah; Hilmi Agni Ruhiyat; Metha Irmawayani Putri (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Research on academic integrity among final-year students preparing mini-theses is still limited in Indonesia, particularly in Islamic universities. Therefore, this research aimed to assess the influence of spirituality and supervisor support on academic integrity of final-year students at an Islamic university in Bandung. A correlational quantitative method was adopted focusing on the relationship between independent and dependent variables. Using a census method, data was collected from a total of 205 final-year students. The results showed that multiple regression analysis exhibited an F-value of 86.525 with a p-value < 0.05, implying the collective influence of spirituality and supervisor support on academic integrity by 46.1%. These observations showed that spirituality had a greater impact on academic integrity than supervisor support among participants. A detailed explanation of this research was provided in the subsequent sections.